2018
DOI: 10.1111/jvp.12508
|View full text |Cite
|
Sign up to set email alerts
|

A study of the pharmacokinetics and thromboxane inhibitory activity of a single intramuscular dose of carprofen as a means to establish its potential use as an analgesic drug in white rhinoceros

Abstract: The alleviation of pain and prevention of suffering are key aspects of animal welfare. Unfortunately, analgesic drugs are not available for all species. White rhinoceros (Ceratotherium simum), representing one of such species, which survive poaching attempts inflicted with severe facial injuries and gunshot wounds, nonetheless require analgesic support. To improve treatment conditions, this study explored the use of carprofen for the treatment of pain and inflammation in white rhinoceros. The pharmacokinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…To overcome limitations in species specific information, the medical management of the rhino tends to be based on information available for the horse. However, the findings of a recent study we undertook in rhinos showed that the half-life of elimination for carprofen was more than threefold longer than that in the horse ( Leiberich et al, 2018 ). This made us question the validity of the horse as a model.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To overcome limitations in species specific information, the medical management of the rhino tends to be based on information available for the horse. However, the findings of a recent study we undertook in rhinos showed that the half-life of elimination for carprofen was more than threefold longer than that in the horse ( Leiberich et al, 2018 ). This made us question the validity of the horse as a model.…”
Section: Discussionmentioning
confidence: 95%
“…While from a general phylogenetic point of view the horse is regarded as one of the closest related species to the rhinoceros ( Tougard et al, 2001 ), we questioned whether it is correct to treat rhinos like large horses. Studies ( Leiberich et al, 2018 ; M. Leiberich, 2018, unpublished data) have recently been undertaken in order to elucidate this issue. Enrofloxacin and carprofen, two potential drugs for the antimicrobial and analgesic treatment of poaching victims and other injured white rhinos, were evaluated in plasma pharmacokinetic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 18,000 southern white rhinoceros ( Ceratotherium simum simum , SWR) inhabit wild and semi‐wild environments (Emslie et al, 2019) as an important apex consumer in the savannas of southern Africa (Cromsigt & te Beest, 2014; Emslie et al, 2019). These wild populations have been declining since 2012 due to increased poaching (Emslie et al, 2019), and each year approximately 200 to 300 SWR are found alive after poaching attacks, often with gunshot wounds or wounds to their frontal and nasal bones (Leiberich et al, 2018). Appropriate medical management of these injuries following systemic stabilization includes wound lavage and effective analgesia (Meyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only two NSAIDs, carprofen (Leiberich, Krebber, et al, 2018) and flunixin meglumine (East et al, 2019), have been investigated for use in rhinoceros. A single 1 mg/kg intramuscular injection in SWR of carprofen reduced thromboxane B 2 activity for 48 h and had an elimination half-life (T 1/2 ) of 106 h, which is the longest reported T ½ for that drug in any mammalian species (Leiberich, Krebber, et al, 2018). The T 1/2 of a single oral dose of flunixin meglumine in SWR was determined to be approximately 8 h, which is over 5 times the T ½ of the same dose reported in horses (East et al, 2019).…”
Section: Introductionmentioning
confidence: 99%